2022
DOI: 10.3390/businesses3010001
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Digital Technologies in Construction Companies: Establishing a Holistic Process which Addresses Current Barriers

Abstract: Digital technologies are being introduced in all areas of the construction industry with the overarching goals of increasing productivity while simultaneously simplifying work and reducing errors. Nevertheless, their use and the associated implementation in construction companies is currently still inhibited. One reason for this is the lack of a holistic implementation process for digital technologies. Therefore, the aim of this paper is to deliver a concept for such a holistic digital-technology-implementatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…For logistics patterns in the construction industry, the lack of data and poor data quality was recognized (Guerlain et al, 2019b;Sezer and Fredriksson, 2020) and the need for data collection (Brusselaers et al, 2020) as well as data sharing (Morel et al, 2019) was given high priority for future research and practice. Acquisition of data is thereby facing particular difficulties, since data on transportation and construction logistics processes are spread among various stakeholders due to the fragmented nature of the construction industry and are yet not fully digitalized (McKinsey, 2016;Schnell et al, 2022). Furthermore, data collection over time is intrinsically not required these days and available documentations are missing essential information, e.g., on the suppliers locations or the routing of the delivery vehicle (Brusselaers et al, 2020).…”
Section: In-depth Content Analysis Of Literaturementioning
confidence: 99%
“…For logistics patterns in the construction industry, the lack of data and poor data quality was recognized (Guerlain et al, 2019b;Sezer and Fredriksson, 2020) and the need for data collection (Brusselaers et al, 2020) as well as data sharing (Morel et al, 2019) was given high priority for future research and practice. Acquisition of data is thereby facing particular difficulties, since data on transportation and construction logistics processes are spread among various stakeholders due to the fragmented nature of the construction industry and are yet not fully digitalized (McKinsey, 2016;Schnell et al, 2022). Furthermore, data collection over time is intrinsically not required these days and available documentations are missing essential information, e.g., on the suppliers locations or the routing of the delivery vehicle (Brusselaers et al, 2020).…”
Section: In-depth Content Analysis Of Literaturementioning
confidence: 99%
“…Through interviews and case studies, Ibrahim et al [5] identified the obstacles that hinder the adoption of digital software by construction consultants. Peter et al [6] studied holistic digital technology implementation and delivered a process that addresses the current barriers for construction companies. Osunsanmi et al [7] revealed a high willingness of construction professionals to adopt new technologies for construction projects.…”
Section: Introduction 1research Backgroundmentioning
confidence: 99%
“…Currently, digitalization and digital transformation are actively expanding into various areas of human activity, and researchers are identifying urgent problems and offering new solutions regarding digital environments in industry [1,2], economics [3,4], medicine [5,6], ecology [7,8], education [9,10], etc.…”
Section: Introductionmentioning
confidence: 99%